The usage of singular and plural forms of address in Lithuanian - Ivanauskaitė, Aleksandra; Hilbig, Inga (Taikomoji kalbotyra, 2023)
This paper investigates the usage of singular and plural forms of address in contemporary Lithuanian. The object of the research is the pronouns tu and jūs, and second-person verbs. The aim of the present study is to analyze how and why singular and plural forms of address are used and which social and psychological factors determine this usage. The research data consists of 111 discourse completion tests filled by university students. For a deeper insight, 6 semi-structured in-depth interviews with students and young people who have just finished their studies were also conducted. Quantitative and qualitative research methods were combined for both data collection and analysis.Based on the results, it can be concluded that the distribution of forms of address in situations where the sociolinguistic and pragmatic choice was not obvious was approximately equal. Statistically significant variables were found to be sex and age. However, as the qualitative aspect of the study reveals, the usage of these forms depends on diverse and subtle variables, including social distance, relative power, and age, as well as their interaction within specific communicational situations. The study confirms that plural forms of address generally convey respect, formality, and polite distance, while singular forms indicate friendliness, intimacy, and familiarity. Nevertheless, both formal and informal forms of address can also be employed as impoliteness strategies. In some cases, the switch between the forms of address is caused by mutual agreement, while in others, it occurs on its own and indicates changes in social or psychological circumstances. The choice between singular and plural forms of address is often complex and not always fluent; therefore, interlocutors may seek to avoid them altogether and navigate a delicate balance between formal and informal ways of addressing people.
Keywords: linguistic politeness; positive and negative politeness; forms of address; tu, jūs; pronouns